The diagnostic process from primary care to child and adolescent mental healthcare services: the incremental value of information conveyed through referral letters, screening questionnaires and structured multi-informant assessment - Semiha Aydin; Bart M. Siebelink; Matty R. Crone; Joost R. van Ginkel; Mattijs E. Numans; Robert R. J. M. Vermeiren; P. Michiel Westenberg (BJPsych Open, 2022)
Background A variety of information sources are used in the best-evidence diagnostic procedure in child and adolescent mental healthcare, including evaluation by referrers and structured assessment questionnaires for parents. However, the incremental value of these information sources is still poorly examined.